Phenol oxidase activation in Drosophila: a cascade of reactions. - Seybold, W.D.; Meltzer, P.S.; Mitchell, H.K. (Biochemical Genetics, 1975)
Our earlier evidence concerning the complexity of the activation process for Drosophila phenol oxidase has been confirmed by separation and purification of six proteins involved. This is a minimal number required in a reaction series or cascade to yield active enzyme, and at least two more proteins are known to be involved. A simpler system involving only the last step with one precursor and one activation as has been reported in the literature is consistent with the cascade picture, but the whole complex system must be considered when dealing with genetic and developmental regulation of pigmentation and sclerotization. Details are given for partial or complete purification of six of the proteins involved and evidence for their modes of interaction is presented.